Amino acid transmitters and the neural control of feeding and energy homeostasis - Dicken, Matthew S., author; Hentges, Shane T., advisor; Tamkun, Michael M., committee member; Amberg, Gregory C., committee member; Tjalkens, Ronald B., committee member (Colorado State University. Libraries, 2016)
Consuming the correct number of calories to maintain a healthy bodyweight is a delicate balancing act between intake and energy expenditure, and humans in modern society seem to have a keen knack for throwing the balance off-center. In the U.S. alone, more than 1/3 of adults are obese based on the body mass index scale, and $147 billion is the estimated annual medical cost for obesity in the United States. On the other end of the feeding spectrum, anorexia in the U.S. has been steadily rising since the 1960s, and has the highest mortality rate of any mental illness. While great strides have been made in understanding the neuronal regulation of energy balance, there is a need to more fully understand the homeostatic systems within the hypothalamus that are so powerful that they are able to drive individuals to poor health or death, often even in the face of consciously fighting their urges. Two groups of functionally opposed neurons contained within the arcuate nucleus of the hypothalamus, Neuropeptide Y / Agouti-related peptide (NPY/AgRP) and proopiomelanocortin (POMC) cells (the so-called first order feeding neurons), have been extensively studied for their roles in energy homeostasis—mostly through research into the peptides they are named after. There is clear evidence that peptides play an essential role for the function of NPY/AgRP and POMC cells, but what about simple amino acid transmitters? While it is known that GABA is packaged and released by NPY/AgRP cells and that this release is relevant to feeding behavior, there is still a dearth of information about this aspect of the circuitry, very much an area waiting to be mined. This study focuses on better understanding the functional release and relevance of amino acid transmitters packaged in both NPY/AgRP and POMC cell populations. Evidence is presented here for the conclusive release of both GABA and glutamate from POMC cells within intact circuitry. For NPY/AgRP neurons, evidence is presented for a shift in functional release of GABA from these neurons onto POMC cells depending on feeding state, corroborated by concurrent in situ hybridization experiments. Using a combination of electrophysiology and in situ hybridization approaches, evidence is also provided that mRNA levels of glutamate decarboxylase can act as a general proxy for functional GABA release. Altogether, these results indicate that amino acid transmitters play a significant role in first order feeding neuron physiology. Not only does this warrant further study on the significance of each transmitter alone and their purpose in comparison with the peptides released, but also the interplay between POMC cell and NPY/AgRP cell amino acid transmitters and their many shared downstream targets. Imbalances in proper glutamatergic and GABAergic signaling may significantly contribute to obesity, and advancing this area of study could lead to correcting those imbalances to restore healthy energy homeostasis.